2017
DOI: 10.1371/journal.pone.0177002
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of cotyledon excision and nursery fertilization on root growth, nutrient status and outplanting performance of Quercus variabilis container seedlings

Abstract: Artificial excision of the distal part of acorns in order to promote germination is well researched in oak seedling cultivation studies. However, studies of combined effects of cotyledon excision and nursery fertilization on container seedlings are lacking, especially for seedling root growth and outplanting performance. This study aimed to explore the main effects of cotyledon excision on Quercus variabilis seedling emergence characteristics and demonstrated the combined effects of cotyledon excision and nurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 36 publications
1
12
0
1
Order By: Relevance
“…The use of small acorns resulted in low seedling emergence, which is similar to the findings for other oak species (Tripathi and Khan 1990;Thcklin and McCreary 1991;Pesendorfer 2014;Sánchez-Montes de Oca et al 2018). It is possible that small acorns in our study stored insufficient resources (Table 1) to support germination and emergence (Flint and Palmblad 1978;Tripathi and Khan 1990), akin to the way in which experimental reduction of cotyledon reserves results in poor seedling emergence (Giertych and Suszka 2011;Liu et al 2012;Shi et al 2017). In addition, small acorns in our study had lower MC than medium-sized and large acorns (Table 1).…”
Section: Effects Of Acorn Size and Nursery Fertilization On Seedling supporting
confidence: 83%
See 1 more Smart Citation
“…The use of small acorns resulted in low seedling emergence, which is similar to the findings for other oak species (Tripathi and Khan 1990;Thcklin and McCreary 1991;Pesendorfer 2014;Sánchez-Montes de Oca et al 2018). It is possible that small acorns in our study stored insufficient resources (Table 1) to support germination and emergence (Flint and Palmblad 1978;Tripathi and Khan 1990), akin to the way in which experimental reduction of cotyledon reserves results in poor seedling emergence (Giertych and Suszka 2011;Liu et al 2012;Shi et al 2017). In addition, small acorns in our study had lower MC than medium-sized and large acorns (Table 1).…”
Section: Effects Of Acorn Size and Nursery Fertilization On Seedling supporting
confidence: 83%
“…This suggests that there is an acorn size threshold below which seedling nutrient status and growth strongly decrease. Poor growth and nutrition of small-acorn seedlings may reflect the smaller amount of resources contained within small acorns (Shi et al 2017(Shi et al , 2018a (Table 1).…”
Section: Effects Of Acorn Size and Nursery Fertilization On Seedling mentioning
confidence: 99%
“…In the current study, the variations in the values of the dimensional scarification index (0.15 to 0.42) and the mass scarification index (0.12 to 0.35) did not influence the germination capacity of differently sized acorns. Shi et al [51] reported the best results where acorns were reduced in length by one-third to one-half. In the cited study, scarification increased fertilizer absorption by oak acorns and seedlings grown in a nursery.…”
Section: Discussionmentioning
confidence: 99%
“…Seed consumption during early stages of seedling establishment (i.e. removal of seeds from seedlings) has been reported in a number of plant species (Côté, Ferron, & Gagnon, 2003;Gómez et al, 2003;Perea & Gil, 2014;Shi, Bloomberg, Li, Su, & Jia, 2017;Wahungu, Catterall, & Olsen, 2002). However, compared with many species, the cotyledons in germinating acorns of most oak species still contain substantial nutritional reserves well beyond seedling establishment (Perea, San Miguel, & Gil, 2011;Yi et al, 2013;Yi, Wang, Liu, Liu, & Zhang, 2015).…”
mentioning
confidence: 99%
“…However, tolerance to post-germination acorn predation has not been well studied in species with different life-history traits (Bossema, 1979;Gómez et al, 2003Gómez et al, , 2008. Fewer studies consider whether seedlings can sustain post-dispersal seed predation across multiple species (Andersson & Frost, 1996;Shi et al, 2017;Wahungu et al, 2002). Moreover, we have limited knowledge of the threshold at which the young seedlings of oak species can survive without the support of acorn reserves (Hanley, Fenner, Whibley, & Darvill, 2004), though cotyledon removal has negative effects on seedling performance (Branco, Branco, Merouani, & Almeida, 2002;García-Cebrián et al, 2003;Korstian, 1927;Shi, Villar-Salvador, Jacobs, Li, & Jiang, 2018).…”
mentioning
confidence: 99%